Peran Keterlibatan Karyawan, Lingkungan Kerja dan Pembelajaran Organisasi terhadap Komitmen Organsisasi - Holong Saor Nababan; Ramses Simanjuntak; Diapari S. Putra Pane (University of Merdeka Malang, 2022)
This research aims to find out the effect of employee engagement, work environment, and organizational learning on the organization's commitment to manufacturing companies in The East Jakarta Industrial Park (EJIP) Bekasi Industrial Estate. This research is with a quantitative approach, and this type of research is explanatory research. The study was conducted on 17 manufacturing companies in the EJIP Bekasi industrial area with a population of 2757 employees with a sample of 350 respondents. Data processing uses SPSS and Structural Equation Modeling (SEM) programs with Lisrel software. The results showed that employee involvement in the company has a positive and significant effect on organizational commitment. The work environment has a positive and significant on employee commitment. Organizational learning has a positive and significant on organizational commitment. This research advice, the company engages employees in various tasks will provide an opportunity to optimize its potential and will add a sense of belonging to the company. Improvements in the physical and non-physical work environment, create a calm and conducive work atmosphere to increase organizational commitment. Likewise, the application of organizational learning for employees needs to improve their knowledge, skills, and expertise. Leaders need to support organizational learning for employees. They have a self-development program and increase the organization's commitment.